2010
DOI: 10.2147/ijn.s10778
|View full text |Cite
|
Sign up to set email alerts
|

Study on effect of peptide-conjugated near-infrared fluorescent quantum dots on the clone formation, proliferation, apoptosis, and tumorigenicity ability of human buccal squamous cell carcinoma cell line BcaCD885

Abstract: submit your manuscript | www.dovepress.com Dovepress 401 O r I g I N A L r e S e A r c h open access to scientific and medical research Open Access Full Text Article 10778Study on effect of peptide-conjugated near-infrared fluorescent quantum dots on the clone formation, proliferation, apoptosis, and tumorigenicity ability of human buccal squamous cell carcinoma cell line BcaCD885Deping Sun Abstract: Quantum dots (QDs) have shown great development potential in noninvasive imaging and monitoring of cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Previous studies have demonstrated that QDs at the experimental concentration are not cytotoxic and do not affect the growth and differentiation of the live cells (3,4,23). Our previous studies have also shown that labeling of cancer cells with NIRF-QDs do not affect their growth, proliferation, apoptosis, invasion, metastasis or the ability to form tumors (10,(24)(25)(26). Clinically, optical examination is a safe, simple and economical approach (18,27).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have demonstrated that QDs at the experimental concentration are not cytotoxic and do not affect the growth and differentiation of the live cells (3,4,23). Our previous studies have also shown that labeling of cancer cells with NIRF-QDs do not affect their growth, proliferation, apoptosis, invasion, metastasis or the ability to form tumors (10,(24)(25)(26). Clinically, optical examination is a safe, simple and economical approach (18,27).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have suggested that biologically functionalized QDs have excellent biological compatible and are water soluble (3,4,23). In addition, they do not cause side effects on live subjects and do not affect cellular growth, differentiation and function within the range of experimental doses (3,4,10,(23)(24)(25)(26). However, the core of QDs is typically made up of heavy metal elements, e.g., plutonium, cadmium and mercury.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: Ab, antibodies; BcacD885, human buccal squamous cell carcinoma cell line; egFr, epidermal growth factor receptor; qD800, quantum dots with a maximal emission wavelength of 800 nm. [6][7][8][9][10][11] In this study, we intravenously injected QD800-EGFR Ab probe to target EGFR, which is highly expressed by OSCC. In-vivo imaging and tumor immunohistochemical analysis showed that QD800-EGFR Ab probe can specifically bind BcaCD885 cells with high level expression of EGFR.…”
Section: Visible In-situ and In-vivo Imaging Of Oscc By Qd800-egfr Abmentioning
confidence: 99%
“…In addition, any emission spectrum from ultraviolet to near-infrared (or from blue to red) under the same excitation wavelength of light can be obtained by changing the particle size of QDs. [6][7][8] These optical characteristics of QDs are not possessed by any of the current fluorescent probes, including a variety of organic fluorescent dyes and fluorescent proteins. Particularly, the fluorescence of recently developed QDs with an emission of near-infrared wavelength from 700 nm to 900 nm has strong penetration in human tissues, which is extremely suitable for visible in-vivo medical imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation